Endobronchial ultrasound-guided transbronchial needle aspiration use for subclassification and genotyping of lung non-small-cell carcinoma - Diab, Khalil (2018)
OBJECTIVES:Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the primary method for the diagnosis and staging of lung cancer. The purpose of this study was to assess the yield of EBUS-TBNA in the subtyping and genotyping of lung adenocarcinoma. METHODS:Sixty-nine patients at Indiana University Hospital and Sidney and Lois Eskenazi Hospital with possible or confirmed lung adenocarcinoma underwent EBUS-TBNA using a 21-gauge Olympus needle without suction. Samples were sent for molecular testing after rapid onsite specimen evaluation. A total of 6 to 10 passes were placed in a cell block. RESULTS:Sixty-nine samples from patients with non-small-cell lung cancer were sent for molecular testing for epidermal growth factor receptor. Results were obtained in all of the patients. Mutations were found in three patients (4.3%). Fifty-eight samples were sent for V-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (100% yield), 10 of which had mutations (17.2%). Fifty-one samples were sent for proto-oncogene tyrosine-protein kinase ROS testing (1 [7.8%] mutant). Tissue samples were inadequate in three patients (94.1% yield). Sixty-three samples were sent for anaplastic lymphoma receptor tyrosine kinase testing (3 [4.8%] mutant, 6 [9.5%] inadequate, 90.5% yield). CONCLUSIONS:EBUS-TBNA with a 21-gauge needle is appropriate for the analysis of multiple mutations and the genotyping of lung adenocarcinoma.